A geospatial approach to mapping and assessment of urban ecosystem services in Bulgaria - Stoyan NEDKOV; Miglena ZHIYANSKI; Bilyana BORISOVA; Mariyana NIKOLOVA; Svetla BRATANOVA-DONCHEVА; Lidia SEMERDZHIEVA; Ivo IHTIMANSKI; Petar NIKOLOV; Zvezdelina AIDAROVA (European Journal of Geography)
The mapping of ecosystem services is essential for understanding how ecosystems contribute to human wellbeing. The EU Biodiversity Strategy to 2020 requires the member states to map and assess the state of ecosystems and their services. Urban landscapes provide various services and their mapping necessitates prioritization, integration of data and application of geospatial approaches. In this paper, we focus on the geospatial approach used to assess and quantify the ecosystem services provided by the urban ecosystems and its possibilities for producing maps at multiple scales. The assessment of ecosystem services is based on various indicators, which rely on different data sources with their own origins, scales, and levels of precision. We develop seven GIS-based approaches that comprise different procedures and tools to arrange the available data and produce ES maps.